Malignant melanoma metastasis as a rare cause of abdominal pain - Kriegler, T; Dušek, T; Ninger, V; Hanousek, P; Podhola, M (Rozhledy v chirurgii, 2024)
The authors present the case of a 71-year-old female patient who was operated on for 16 days of abdominal pain. The work points to malignant melanoma as a rare cause of abdominal pain and then shows the inscrutability of malignant melanoma and the importance of a multidisciplinary approach to this type of disease including subsequent dispensary by an oncologist. The emphasis on the prevention of this disease is an integral part of this approach.
Keywords: Gastrointestinal tract; abdominal pain; Skin Neoplasms; metastasis; multidisciplinary approach; Aged; senioři; malignant melanoma; Melanoma; bolesti břicha; lidé; ženské pohlaví; gastrointestinal tract; Humans; melanoma; Abdominal Pain; Abdominal pain; nádory kůže; Female; melanom